Online trajectory replan for gliding vehicle considering terminal velocity constraint - Kim, Youngil; Cho, Namhoon; Park, Jongho; Kim, Youdan (IEEE, 2022)
Controlling the terminal velocity can improve the effectiveness of guided missiles. In particular, a ballistic missile propelled by solid rocket motors can successfully accomplish its mission when it hits the target at an appropriate speed. In this study, a method for modifying the trajectory of gliding vehicle, i.e., gliding ballistic missiles is proposed to meet the terminal velocity constraint by reflecting the effects of the environment during a flight. The proposed framework consisting of trajectory generation and dynamic propagation compensates for errors due to uncertainties in real time. The trajectory generation step provides various trajectories that satisfy the given constraints based on information about the current state. The dynamic propagation step efficiently predicts the terminal velocity for each of the generated trajectories and finds the trajectory with the lowest terminal speed error. A numerical simulation is performed considering various conditions to demonstrate the performance of the proposed method.
Keywords: Terminal Velocity Constraint; Trajectory Generation; Dynamic Propagation